До питання про інверсний аналіз електричних кіл - Ромашко, В.Я.; Батрак, Л.М. (Технічна електродинаміка, 2012)
The features of tasks of analysis, inverse analysis and authentications that arise up at research of electric circles are analysed. Almost complete absence is marked in educational literature of list about an inverse analysis and authentication. The possible going is considered near an inverse analysis on the example of linear capacitanceresistance circles and methodologies of such analysis are offered. Expediency of the use of secondary parameters of electric chain is reasonable at the decision of tasks of inverse analysis and authentication.